Human Resource Development in Improving Employee Performance at Bawaslu Padang Pariaman - yoga tri rizki ananda; John Ver; Riska Kurnia Dewi (Jurnal MSDA (Manajemen Sumber Daya Aparatur), 2025)
This study examines human resource development through training programs to improve the performance of Bawaslu employees in Padang Pariaman Regency. The main issue is the limited evaluation of training effectiveness, which reduces its usefulness for policy and strategic decision-making. Using a survey with purposive sampling involving all employees, the data were analyzed through reduction, presentation, and conclusion drawing. The results show that the training is relevant to core tasks, enhances competencies, and helps employees meet performance standards, but has not significantly improved productivity. Thus, improvements are needed in training budget planning, the development of measurable performance indicators, and the implementation of key performance indicators (KPIs) to assess training outcomes and support sustained competency development. These findings are expected to guide Bawaslu in formulating more effective HR development strategies.